The anthropometric, physical, and relative age characteristics of an English Premiership rugby union academy - Francesco Dimundo; Matthew Cole; Richard C. Blagrove; Alexander B. T. McAuley; Kevin Till; Mike Hall; Daniele Pacini; Adam L. Kelly (International Universities Strength and Conditioning Association, 2021)
Long-term athlete development is a primary focus for the England Rugby Football Union (RFU). The purpose of this study was to explore the anthropometric, physical, and relative age characteristics of rugby union academy players based on age group and playing position. Seventy-eight participants were examined for height, body mass, 10 and 20 m sprint, countermovement jump, reactive strength index, aerobic capacity, isometric hip extension, dominant handgrip strength, and birth quartile (BQ) across three age categories (i.e., under-16, under-18, and under-21) and two positions (forwards and backs). ANOVA and Kruskall-Wallis analysis were used to examine differences across each age category and position. TukeyHSD and Dunn's test with Bonferroni correction was used for further post-hoc analysis. BQ distributions were compared against national norms using chi-square analysis. Results revealed that both older forwards (P=0.005) and backs (P=0.002) had significantly greater body mass, maximal aerobic capacity, and power compared to younger players. However, older forwards had slower 10 m sprint times compared to younger forwards. Moreover, relatively older players were significantly overrepresented across all age groups when compared to relatively younger players. Findings suggest that: (a) players should aim to develop greater parameters of body mass and aerobic capacity; (b) forwards should aim to develop acceleration and strength; (c) backs should aim to develop power and quickness; (d) players need to develop anthropometric and physical qualities and differences are apparent by age and position; and, (e) coaches should consider relative age when recruiting and developing young players. Key words: Talent identification; Talent development; Expertise; Physical development; Physiological profile; Rugby football